2024
DOI: 10.1161/circresaha.123.323679
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Neuromodulation of an Anti-Inflammatory Pathway at the Spleen Improves Experimental Pulmonary Hypertension

Stefanos Zafeiropoulos,
Umair Ahmed,
Alexandra Bekiaridou
et al.

Abstract: BACKGROUND: Inflammation is pathogenically implicated in pulmonary arterial hypertension; however, it has not been adequately targeted therapeutically. We investigated whether neuromodulation of an anti-inflammatory neuroimmune pathway involving the splenic nerve using noninvasive, focused ultrasound stimulation of the spleen (sFUS) can improve experimental pulmonary hypertension. METHODS: Pulmonary hypertension was induced in rats either by Sugen 5416 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Spleen-Focused Ultrasound Neuromodulation in PAH the study by Zafeiropoulos et al 11 did not replicate the published effects of sFUS on cytokine production, 10 observing no significant changes in IL-1β, TNF, or other inflammatory cytokines in the spleen, circulation, or lungs of PAH rodents. The precise analysis of circulating and pulmonary/splenic residential Th17, regulatory T cells, and macrophages could address the remaining question about the impact of sFUS on the function of immune cells.…”
Section: Rafikova Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…Spleen-Focused Ultrasound Neuromodulation in PAH the study by Zafeiropoulos et al 11 did not replicate the published effects of sFUS on cytokine production, 10 observing no significant changes in IL-1β, TNF, or other inflammatory cytokines in the spleen, circulation, or lungs of PAH rodents. The precise analysis of circulating and pulmonary/splenic residential Th17, regulatory T cells, and macrophages could address the remaining question about the impact of sFUS on the function of immune cells.…”
Section: Rafikova Et Almentioning
confidence: 90%
“…In this issue of the Journal Circulation Research, Zafeiropoulos et al 11 implemented this innovative technology to investigate the therapeutic effect of focused ultrasound stimulation of the spleen (sFUS) in experimental PH (Figure). Using rats with SuHx-and monocrotalineinduced PH, the authors demonstrated that sFUS treatment led to a significant reduction in right ventricular systolic pressure, improved right ventricular hypertrophy, and decreased remodeling of small PAs with no effect on mean arterial pressure, heart rate, and right ventricular end-diastolic pressure.…”
Section: Article See P 41mentioning
confidence: 99%